2015
DOI: 10.1597/12-171
|View full text |Cite
|
Sign up to set email alerts
|

Association between Dental Arch Widths and Interarch Relationships in Children with Operated Unilateral Complete Cleft Lip and Palate

Abstract: Operated UCLP patients with more severe sagittal discrepancies tend to show more severe transverse maxillary arch deficiencies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 20 publications
(23 reference statements)
0
3
1
Order By: Relevance
“…The disparity between our results and those of investigations involving linear, area, and volumetric assessments by Bittencourt et al [32] and Generali et al [33] is also noteworthy. These studies reported maxillary arch constriction in the cleft area and width similarity in the molar region in preadolescent patients with UCLP compared to controls.…”
Section: Discussioncontrasting
confidence: 99%
“…The disparity between our results and those of investigations involving linear, area, and volumetric assessments by Bittencourt et al [32] and Generali et al [33] is also noteworthy. These studies reported maxillary arch constriction in the cleft area and width similarity in the molar region in preadolescent patients with UCLP compared to controls.…”
Section: Discussioncontrasting
confidence: 99%
“…[3][4][5] Recent inter-centre studies observed high frequencies of poor interarch relationship in patients with CUCLP. 6,7 Multiple factors may cause maxillary growth deficiency, including surgical techniques, age, number of surgeries, surgeon´s skill, familial growth pattern and initial cleft width. [8][9][10] In particular, initial cleft width in patients with CUCLP varies widely.…”
Section: Introductionmentioning
confidence: 99%
“…After primary surgeries, the growth pattern changes, resulting in maxillary retrusion and in maxillary vertical and transversal deficiency 3‐5 . Recent inter‐centre studies observed high frequencies of poor interarch relationship in patients with CUCLP 6,7 . Multiple factors may cause maxillary growth deficiency, including surgical techniques, age, number of surgeries, surgeon´s skill, familial growth pattern and initial cleft width 8‐10 .…”
Section: Introductionmentioning
confidence: 99%
“…1 BCLP causes serious esthetical, functional, anatomic and psychosocial disorders requiring early surgery repair. 2 The rehabilitation protocol for BCLP includes lip and palate repair, alveolar bone graft and orthodontics, isolated or combined with orthognatic surgery. 3 At birth, a patient with complete BCLP presents severe convex facial profile due to premaxilla projection.…”
Section: Introductionmentioning
confidence: 99%